2010
DOI: 10.1103/physrevlett.105.135005
|View full text |Cite
|
Sign up to set email alerts
|

Control of Gradient-Driven Instabilities Using Shear Alfvén Beat Waves

Abstract: A new technique for manipulation and control of gradient-driven instabilities through nonlinear interaction with Alfvén waves in a laboratory plasma is presented. A narrow, field-aligned density depletion is created in the Large Plasma Device (LAPD), resulting in coherent, unstable fluctuations on the periphery of the depletion. Two independent shear Alfvén waves are launched along the depletion at separate frequencies, creating a nonlinear beat-wave response at or near the frequency of the original instabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…An experiment was performed in which two Alfvén waves were broadcast along a filamentary density depletion on which a coherent unstable mode was present. 119 The beating Alfvén waves were found to resonantly drive the instability when the beat frequency was tuned to match the unstable mode frequency. More interestingly, it was found that when the beat frequency was tuned to resonantly drive nearby (in frequency) damped modes, the original unstable mode was suppressed.…”
Section: -15mentioning
confidence: 99%
“…An experiment was performed in which two Alfvén waves were broadcast along a filamentary density depletion on which a coherent unstable mode was present. 119 The beating Alfvén waves were found to resonantly drive the instability when the beat frequency was tuned to match the unstable mode frequency. More interestingly, it was found that when the beat frequency was tuned to resonantly drive nearby (in frequency) damped modes, the original unstable mode was suppressed.…”
Section: -15mentioning
confidence: 99%
“…Extensive prior work has focused on the properties of linear Alfvén waves [5,[28][29][30]. Studies of the nonlinear properties of Alfvén waves have also been performed on the LAPD; in these experiments, two launched Alfvén waves nonlinearly interact to drive a nonresonant mode [31], a drift wave [32], an acoustic mode [33,34], or an Alfvén wave [35].…”
mentioning
confidence: 99%
“…24 In a second set of experiments, the copropagating beat mode is driven near the frequency of existing drift wave turbulence; the beat mode is then found to couple to the drift modes, altering the drift wave frequency spectrum. 25 In this paper, the first laboratory observations of the Alfv en-acoustic mode coupling at the heart of the parametric decay instability described in Dorfman and Carter 26 are presented in detail. Counter-propagating shear Alfv en waves are launched from antennas and allowed to interact nonlinearly.…”
Section: Introductionmentioning
confidence: 97%
“…5,[21][22][23] Studies of the nonlinear properties of Alfv en waves have also been performed on LAPD. 24,25 For instance, the interaction between two co-propagating Alfv en waves may nonresonantly drive a quasimode in the plasma; this quasimode then couples to the original waves to produce a spectrum of Alfv enic sidebands. 24 In a second set of experiments, the copropagating beat mode is driven near the frequency of existing drift wave turbulence; the beat mode is then found to couple to the drift modes, altering the drift wave frequency spectrum.…”
Section: Introductionmentioning
confidence: 99%